An unusual cause of hoarseness of voice in a pediatric patient – A case report - Swain, Santosh Kumar; Sahu, Mahesh Chandra; Samantray, Kabikanta (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Reinke’s edema (RE) is a benign polypoidal lesion of the vocal folds. The vocal folds show a white and translucent edema, confined into the superficial lamina propria. The lesions usually affect both vocal folds with fusiform appearance and even mobile during phona¬tion. Hoarseness of voice is the most common clinical presentation in RE. Patients usually present with characteristic low, raspy, or rough voice. RE is often associated with smoking habit, gastroesophageal reflux and voice abuse. RE is typically occurs in middle-aged male or post-menopausal women who have a long-term history of cigarettes smoking, whereas RE is uncommon among children. We hereby report a case of RE in a 10-year-old boy.